The nature and evaluation of complex potential competitiveness of innovative business structures - K. Y. Reshetov (Путеводитель предпринимателя)
This article is devoted to the determination of the entity and assessment of complex potential competitiveness of innovative business structures. For this early work approaches to the analysis of the structure of the innovative potential of enterprises. The author examines the essence and the author’s definition of complex potential innovative business structures, and it did so with regard to the functioning of the main categories of innovation-active enterprises. At the end of the article presents the method of complex estimation of potential competitiveness of innovative business structures.